Bipolar-Interface Hydrogen Fuel Cells: A Review and Perspective on Future High-Performance, Low Platinum-Group Metal Content Designs - Seeberger, Dominik; Hartert, Adrian; Mayerhöfer, Britta; Thiele, Simon (ChemElectroChem, 2021)
This Review elucidates the state-of-the-art, challenges, and future prospects for bipolar-interface-based fuel cells (BPIFCs), focusing on hydrogen-based systems. On the one side, it provides a summary of state-of-the-art design strategies for BPIFCs from different fields of application. On the other hand, it identifies the two most pivotal areas for a future understanding that particularly refer to the changed mass transport situations introduced by the bipolar fuel cell design, that is, the water management and the bipolar interface layer itself. All operation-relevant components such as the gas diffusion layers, catalyst layers, and membrane designs are discussed within the framework of these two main areas. As non-platinum-group metal (PGM) oxygen reduction is one of the key benefits of bipolar hydrogen fuel cells, a particular focus is put on this configuration. Several additional challenges that exclusively originate from non-PGM-based catalyst layers and possible mitigation approaches are discussed. One key insight is that these thick layers could take over the role of microporous layers in the future. Finally, we emphasize that there is a strong lack in both theoretical and experimental approaches that improve our understanding of the underlying processes in bipolar fuel cell designs.
CRIS-Team Scopus Importer:2021-03-26
Keywords: alkaline oxygen reduction reaction; bipolar membrane; Fe−N/C; hybrid fuel cells; PGM-free catalysts